从文图学视角看电影《九龙城寨之围城》对香港文化记忆的重构 = Hong Kong cultural memory: a study of the film "Twilight of the Warriors: Walled In" from the perspective of text and images studies - 刘懿萱 Low, Yi Xuan (Nanyang Technological University, 2025)
本文以文图学为理论框架，分析电影《九龙城寨之围城》如何通过视听语言重构香港的文化记忆。研究聚焦影视文本的互文性，探讨影片如何以九龙城寨为空间载体，融合怀旧美学与未来的城市想象，牵引出殖民历史与本土意识的张力。借助数码特效以及角色的肢体和声音，影片将底层抗争与身份焦虑具象化为江湖叙事，既延续港式动作片的类型传统，又作出视觉表达的创新。研究发现，电影成功通过跨媒介传播将城寨符号延伸至公共空间，使其从历史废墟转化为全球化语境下的文化认同媒介。这表明文图学视角能有效揭示商业电影对文化记忆的重构逻辑，为香港电影的研究提供了新范例。This study employs a Text and Image Studies framework to examine how Twilight of the Warriors: Walled In reconstructs Hong Kong’s cultural memory through its audiovisual narrative. By exploring the interplay between visual elements and textual cues, the research analyses how the film transforms the legacy of Kowloon Walled City into a cultural symbol that bridges nostalgia with futuristic urban visions. Through spatial design, character symbolism, and metaphorical imagery, the study reveals a deliberate tension between colonial history and emerging local identity. Moreover, the film’s use of digital effects and expressive performances reframes historical narratives of resistance and identity anxiety within a distinctive cinematic discourse. Extending beyond the screen, its transmedia reach—through fan engagement and public exhibitions—fosters a broader dialogue on heritage in a globalised context. The findings underscore how a Text and Image Studies perspective effectively unravels the mechanisms of cultural memory reconstruction in commercial cinema, offering new insights into Hong Kong’s evolving cultural identity.